H-NS Family Proteins Drastically Change Their Targets in Response to the Horizontal Transfer of the Catabolic Plasmid pCAR1 - Nakamura, Taisuke; Suzuki-Minakuchi, Chiho; Kawano, Hibiki; Kanesaki, Yu; Kawasaki, Shinji; Okada, Kazunori; Nojiri, Hideaki (Frontiers in Microbiology, 2020)
H-NS family proteins regulate the expression of many genes by preferably binding to AT-rich genomic regions and altering DNA topology. They are found in both bacterial chromosomes and plasmids, and plasmid-encoded H-NS family proteins have sometimes been suggested to act as a molecular backup of the chromosomally encoded ones. Pmr is an H-NS family protein encoded on the catabolic plasmid pCAR1, which belongs to incompatibility P-7 group. We have investigated the function of Pmr in Pseudomonas putida KT2440, where two H-NS family proteins (TurA and TurB) encoded on the chromosome are expressed predominantly. Previous transcriptome analyses suggested that TurA, TurB, and Pmr cooperatively regulate numerous genes, but the differentially transcribed genes in KT2440ΔturA(pCAR1), KT2440ΔturB(pCAR1), and KT2440(pCAR1Δpmr) compared with those in KT2440(pCAR1) were somewhat different. Here, we performed RNA sequencing analyses to compare the differentially transcribed genes after the deletion of turA or turB in KT2440, and turA, turB or pmr in KT2440(pCAR1). Three pCAR1-free strains (KT2440, KT2440ΔturA, KT2440ΔturB) and four pCAR1-harbouring strains [KT2440(pCAR1), KT2440ΔturA(pCAR1), KT2440ΔturB(pCAR1), KT2440(pCAR1Δpmr)], grown until the log and stationary phases, were used. In KT2440, TurA was the major MvaT homologue regulating a large number and wide range of genes, and both TurA and TurB were suggested to functionally compensate each other, particularly during the stationary phase. In KT2440(pCAR1), the numbers of differentially transcribed genes after the deletion of turA or turB drastically increased compared to those in KT2440. Notably, more than half of the differentially transcribed genes in KT2440ΔturA and KT2440ΔturB did not overlap with those in KT2440ΔturA(pCAR1) and KT2440ΔturB(pCAR1). This dynamic change could be explained by the acquisition of pCAR1 itself and the expression of Pmr. After pCAR1 was transferred into the host, TurA and TurB could be detached from the chromosome of KT2440 and they could newly bind to pCAR1. Moreover, Pmr could reconstitute the chromosome-binding heteromeric oligomers which were formed by TurA and TurB. Our study revealed that horizontal transfer of a plasmid changes the transcriptional network of the chromosomally encoded H-NS family proteins.